2015
DOI: 10.1523/jneurosci.1910-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Connection of Inflammatory Pain: Pivotal Role of a Pyruvate Dehydrogenase Kinase-Pyruvate Dehydrogenase-Lactic Acid Axis

Abstract: Pyruvate dehydrogenase kinases (PDK1-4) are mitochondrial metabolic regulators that serve as decision makers via modulation of pyruvate dehydrogenase (PDH) activity to convert pyruvate either aerobically to acetyl-CoA or anaerobically to lactate. Metabolic dysregulation and inflammatory processes are two sides of the same coin in several pathophysiological conditions. The lactic acid surge associated with the metabolic shift has been implicated in diverse painful states. In this study, we investigated the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 99 publications
1
61
1
Order By: Relevance
“…For instance, after W6 of CPZ administration we observed a strong reduction of MPs in the corpus callosum. Although most of the remaining MPs still express PDK1 and there is a trend toward decreased PDH activity compared with CTRL, we did not detect a significantly increased production of HP [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate at that time point, which may be explained by the limited sensitivity of HP 13 C MRSI to lower MP number. Furthermore, the lack of increase in the HP [1-13 C]lactate-topyruvate ratios in two of seven mice at W4 (Fig.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…For instance, after W6 of CPZ administration we observed a strong reduction of MPs in the corpus callosum. Although most of the remaining MPs still express PDK1 and there is a trend toward decreased PDH activity compared with CTRL, we did not detect a significantly increased production of HP [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate at that time point, which may be explained by the limited sensitivity of HP 13 C MRSI to lower MP number. Furthermore, the lack of increase in the HP [1-13 C]lactate-topyruvate ratios in two of seven mice at W4 (Fig.…”
Section: Discussioncontrasting
confidence: 60%
“…Novel studies have uncovered a potential underlying mechanism, showing pyruvate dehydrogenase kinase 1 (PDK1) up-regulation in proinflammatory MPs (13,16). Because PDK1 inhibits pyruvate dehydrogenase (PDH), the enzyme that controls pyruvate entrance into the Krebs cycle, PDK1 up-regulation in activated MPs results in increased pyruvate-to-lactate conversion (12,17,18). In line with these observations, lactate has long been suggested as an imaging marker of neuroinflammation in the clinic.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Mechanical and thermal hypersensitivities were assessed to investigate the role of PDK2/4 in formalin‐induced acute inflammation and the subsequent development of pain hypersensitivities. It was previously reported that Pdk2/4 gene deletion in mice did not impair their motor functions, an important prerequisite for proper behavioral testing (Jha et al, ). In addition, the physiologically important responses to acute noxious mechanical and thermal stimulation were not affected in the Pdk2/4 ‐deficient mice, as previously reported (Jha et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…Mitochondrial metabolic aberrations play a crucial role in the ontogeny of diverse pathologies, including cancer (Ramos‐Nino, ), cardiovascular disease (Nisoli et al, ), obesity (Arruda et al, ), diabetes (Sivitz and Yorek, ), and several neurological disorders (Schon and Manfredi, ; Morris and Berk, ). It has recently been demonstrated that a metabolic shift toward lactic acid production plays a pivotal role in the pathogenesis of chronic inflammatory pain (Jha et al, ). In addition, several other studies have implicated this metabolic shift in the pathogenesis of painful peripheral neuropathies (Kim et al, ; Joseph and Levine, ; Fernyhough et al, ), suggesting that functional targeting of mitochondria may be a useful strategy for pain therapy.…”
mentioning
confidence: 99%